Emergency response and planning management system for process industries - Nurul Izzureen, Muhamad Zuraidi (2018)
Unexpected releases of toxic, reactive, or flammable liquids and gases in processes involving highly hazardous chemicals have been reported for many years, in various industries using chemicals with such properties. Regardless of the industry that uses these highly hazardous chemicals, there is a potential for an accidental release any time they are not properly controlled, creating the possibility of disaster. Process safety management (PSM) is addressed in specific standards for the general and construction industries. OSHA's standard emphasizes the management of hazards associated with highly hazardous chemicals and establishes a comprehensive management program that integrates technologies, procedures, and management practices. This study conducted to develop ERP database system that able to manage and track information, documents, and resolution of recommendations related to the process hazards. The system is validated through case study. In conclusion, in order to ensure the company comply with the PSM standard and CIMAH regulations related to ERP, longer time is needed so that the system can be upgraded.